Orthodontic treatment of periodontal patients: challenges and solutions, from planning to retention - Daniela Feu (Dental Press Editora, 2021)
ABSTRACT Introduction: There is an increasing number of adult patients with sequelae of periodontal diseases seeking orthodontic treatment to improve their occlusion and quality of life. However, it is important to highlight that the patient who has vertical bone loss has unique needs, arising from the frequent related pathological migrations. Therefore, it requires an individualized orthodontic treatment in terms of anchorage, biomechanics, and multidisciplinary planning, which raises doubts in the hierarchy of priorities and organization of the treatment plan. Objectives: It was proposed a stratified hierarchy of the needs of orthodontic-periodontal treatment in six levels, which were illustrated with examples of clinical cases in which biomechanical planning and a multidisciplinary approach made it possible to obtain a balanced occlusion, aesthetic improvement and stabilization of the results. Conclusion: Orthodontic treatment of periodontal patients with a multidisciplinary approach is increasingly frequent and should be planned individually, considering bone losses suffered by each patient. Respecting some limitations, it is possible to improve the level of bone insertion, smile aesthetics and masticatory function, to facilitate oral hygiene through the orthodontic treatment of adult patients with little bone support. It is also important to highlight that there are unique aspects in the orthodontic retention in these cases.